Alpha thalassemia allelic frequency in Lebanon. Issue 1 (4th October 2014) - Farra, Chantal; Badra, Rebecca; Fares, Farah; Muwakkit, Samar; Dbaibo, Ghassan; Dabbous, Ibrahim; Ashkar, Hanine; Mounsef, Carla; Abboud, Miguel R.
<x xml:space="preserve">Abstract</x> Background Hemoglobinopathies are the most common reported monogenic disorders worldwide. It is well established that Mediterranean and Arab countries are high risk areas for thalassemia in general, and for alpha thalassemia in particular. Reports of alpha thalassemia gene mutations from the Lebanese population are limited. Procedure We investigated the spectrum of alpha thalassemia mutations in a sample of 70 unrelated Lebanese families. Six different mutations of alpha thalassemia gene were identified. Results The most prevalent mutations were the single gene deletion −α3.7 (43%) and the non‐gene deletion α2 IVS1 [–5nt] (37%). The double deletional determinant –MED was detected only in 14% of thalassemic chromosomes. Conclusion We determined the mutational spectrum of alpha thalassemia which might be used in the future for molecular investigations of the disease in susceptible patients in our population. Pediatr Blood Cancer 2015;62:120–122. © 2014 Wiley Periodicals, Inc.